IMPLEMENTASI WEB SKYSTORE UNTUK MANAJEMEN INVENTORI SUKU CADANG PESAWAT DENGAN FITUR DASHBOARD ANALYTICS DAN SHELF LIFE NOTIFICATIONS MENGGUNAKAN METODE RAD BERBASIS LARAVEL (STUDI KASUS: PT GMF AEROASIA TBK) - Muhamad Iqbal; Meidy Fajar Wahyu (Jurnal Publikasi Ilmu Komputer Terapan, 2026)
Aircraft maintenance operations require accurate and traceable spare-part information, yet satellite-warehouse monitoring may remain dependent on spreadsheets even when an enterprise system is available. This study developed SkyStore, a web-based operational inventory application for a satellite warehouse at PT GMF AeroAsia Tbk. Requirements were identified through non-participant observation, a semi-structured interview with a warehouse supervisor, document review, and analysis of receiving, issuing, return-to-warehouse, in-transit, bin-location, and shelf-life processes. The application was developed through Rapid Application Development using Laravel and MySQL. SkyStore consolidates warehouse transactions, reference data, user permissions, dashboard summaries, import-export functions, and shelf-life notifications without replacing the corporate SAP platform. Functional evaluation covered 59 black-box scenarios across 15 modules, all of which produced the expected results. White-box basis-path evaluation covered 13 independent paths: three in login, five in incoming, and five in shelf-life processing, with cyclomatic complexity values of 3, 5, and 5. All tested paths conformed to the expected outcomes. The findings demonstrate functional and logic-path conformity, but do not establish improvements in processing time, inventory accuracy, or user acceptance because those outcomes were not measured.